Association testing to detect gene–gene interactions on sex chromosomes in trio data - Lee, Yeonok; Ghosh, Debashis; Zhang, Yu (Frontiers in Genetics, 2013)
Autism Spectrum Disorder (ASD) occurs more often among males than females in a 4:1 ratio. Among theories used to explain the causes of ASD, the X chromosome and the Y chromosome theories attribute ASD to X-linked mutation and the male-limited gene expressions on the Y chromosome, respectively. Despite the rationale of the theory, studies have failed to attribute the sex-biased ratio to the signiﬁcant linkage or association on the regions of interest on X chromosome. We further study the gender biased ratio by examining the possible interaction effects between two genes in the sex chromosomes. We propose a logistic regression model with mixed effects to detect gene-gene interactions on sex chromosomes. We investigated the power and type I error rates of the approach for a range of minor allele frequencies and varying linkage disequilibrium between markers and QTLs. We also evaluated the robustness of the model to population stratiﬁcation. We applied the model to a trio-family data set with an ASD affected male child to study gene-gene interactions on sex chromosomes.